Work Environment Transformation and its Impact on Employee Satisfaction: Case Study of PD. Sutera Alam Soleh (SAS) Garut - Santanu, Tita Rachtawati; Utami, Sri (Golden Ratio of Data in Summary, 2024)
A comfortable work environment is one of the important factors in creating employee job satisfaction. High job satisfaction not only improves employee well-being but also contributes to organisational productivity and performance. This study aims to analyse the effect of work environment on employee job satisfaction at PD. Sutera Alam Soleh (SAS) Garut. This research uses quantitative methods with descriptive and associative approaches. The research population is all employees of PD. Sutera Alam Soleh (SAS) Garut which amounted to 80 people, with a saturated sample technique, so that the entire population was used as a sample. Data were collected through a questionnaire containing 18 statement items related to work environment variables and job satisfaction. This research was conducted in Garut in 2024. The results showed that the work environment has a significant influence on employee job satisfaction. Factors such as lighting, cleanliness, air temperature, and good working relationships are proven to support the creation of more optimal job satisfaction. Support from colleagues and superiors is also an important element in building motivation and a conducive work atmosphere. This research implies that companies need to improve the physical and social aspects of the work environment to encourage employee well-being. Future research is recommended to expand the variables and objects of research in order to obtain more comprehensive results.